Security enhanced using honey encryption for private data sharing in cloud - Srinivasu, N; Sahil, Masood; Francis, Jeevan; Pravallika, Sure (International Journal of Engineering and Technology, 2017)
In todayâ€™s modern age technology as there is a production of vast amount of data, it is getting very difficult to store such a vast amount of information. The best way to store this huge data is on cloud. As nowadays business organisations are moving towards cloud to store their data, security remains the primary concern. Is the data securing enough on the cloud or not? One of the ways to secure data on cloud is by providing security on cloud through Honey Encryption. Juels&Ristenrpart introduced honey encryption and showed how to achieve message recovery security even in the face of attacks that can exhaustively try all likely keys. Honey Encryption is a new encryption scheme that ensures the messages decrypted with invalid keys yield a valid looking message. In this paper, we present our implementation of Honey Encryption and apply it to useful real-world scenarios such as providing security to files which are been saved in cloud. The files contain variety of information in it. We also provide assurance against brute force attacks. Â Â